The Physiological Basis of High-Frequency Oscillatory Ventilation and Current Evidence in Adults and Children: A Narrative Review - Miller, Andrew G.; Tan, Herng Lee; Smith, Brian J.; Rotta, Alexandre T.; Lee, Jan Hau (Frontiers in Physiology, 2022)
High-frequency oscillatory ventilation (HFOV) is a ventilation strategy that employs supra-physiologic respiratory rates and low tidal volumes (VT) that approximate the anatomic deadspace. During HFOV, mean airway pressure is set and gas is then displaced towards and away from the patient through a piston. Carbon dioxide (CO2) is cleared based on the power (amplitude) setting and frequency, with lower frequencies resulting in higher VT and CO2 clearance. Airway pressure amplitude is significantly attenuated throughout the respiratory system and mechanical strain and stress on the alveoli are theoretically minimized. HFOV has been purported as a form of lung protective ventilation that minimizes volutrauma, atelectrauma, and biotrauma. Following two large randomized controlled trials showing no benefit and harm, respectively, HFOV has largely been abandoned in adults with ARDS. A multi-center clinical trial in children is ongoing. This article aims to review the physiologic rationale for the use of HFOV in patients with acute respiratory failure, summarize relevant bench and animal models, and discuss the potential use of HFOV as a primary and rescue mode in adults and children with severe respiratory failure.